2020
DOI: 10.1002/cncr.33259
|View full text |Cite
|
Sign up to set email alerts
|

Patient and caregiver agreement on prognosis estimates for older adults with advanced cancer

Abstract: BACKGROUND: Disagreements between patients and caregivers about treatment benefits, care decisions, and patients' health are associated with increased patient depression as well as increased caregiver anxiety, distress, depression, and burden. Understanding the factors associated with disagreement may inform interventions to improve the aforementioned outcomes. METHODS: For this analysis, baseline data were obtained from a cluster-randomized geriatric assessment trial that recruited patients aged ≥70 years who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 66 publications
(142 reference statements)
0
5
0
1
Order By: Relevance
“…For comparison, among the 372/414 patient‐oncologist dyads, 73.9% ( n = 275) were discordant. Among the 354/414 patient‐caregiver dyads with available data, 48% ( n = 170) were discordant [40].…”
Section: Resultsmentioning
confidence: 99%
“…For comparison, among the 372/414 patient‐oncologist dyads, 73.9% ( n = 275) were discordant. Among the 354/414 patient‐caregiver dyads with available data, 48% ( n = 170) were discordant [40].…”
Section: Resultsmentioning
confidence: 99%
“…In this study, it was found that most caregivers (66.4%) were female. Other studies with family caregivers of people with cancer also indicate that they mainly comprise women [17][18][19] . This fact can be attributed to the historical context in which women are primarily responsible for domestic care, as shown in another study 20 .…”
Section: Discussionmentioning
confidence: 97%
“…Assessment of prognostic understanding may occur in the forms of treatment goal or intent, illness perception, curability, and survival. [87][88][89][90] Studies have demonstrated that 50%-73% of older adults with advanced cancer have poor prognostic understanding or that their prognostic understanding differs from that of their oncologist. 87,89,91 In addition, 48%-52% of caregivers of older adults with advanced cancer have differing prognostic understanding from that of the patients and their oncologists.…”
Section: Psychology Cognitive Biases and Informed Consentmentioning
confidence: 99%
“…87,89,91 In addition, 48%-52% of caregivers of older adults with advanced cancer have differing prognostic understanding from that of the patients and their oncologists. 88,89 Poor patient prognostic understanding is associated with receipt of more aggressive care such as chemotherapy at the end of life. 92 In addition, differing prognostic understanding between patients and their caregivers may be associated with lower utilization of hospice services.…”
Section: Psychology Cognitive Biases and Informed Consentmentioning
confidence: 99%